PREVALENCE OF HELMENTHS PARASITES IN VEGETABLES SOLD IN JAMA’ARE METROPOLIS, BAUCHI STATE, NIGERIA - ABUBAKAR, BASHIR MOHAMMED; WABI, AMINA AHMAD; GAGMAN, HALADU A.; MOHAMMED, UMAR AMINU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Consumption of raw vegetables provides essential nutrient to humans. However, eating these vegetables raw without proper washing serve as one of the major factors responsible for high morbidity and mortality globally. The present study aimed to evaluate the prevalence of soiltransmitted helminths (STH) parasites in commonly used vegetables in Jama’are Town, north east Nigeria. A total of 150 fresh raw vegetable samples were obtained from various markets within the study area. Each sample was divided into two groups; unwashed and washed with traditional method. The samples were examined using sedimentation concentration technique and data obtained were analyzed using Chi square in SPSS version 24. The overall prevalence of STH parasites was 22.6%. The unwashed vegetables (29.3%) had more STH contamination than the washed vegetables (16.0%). There was a significantly difference between the occurrence of STH parasites between unwashed and washed vegetables (χ2=14.21, P=0.001). Spinach (26.6%) had the highest prevalence, followed by cabbage, lettuce and carrot which all have 23.3% contamination while green pepper had the least contamination. For the unwashed, spinach (8%) had the highest prevalence while green paper (4.0%) has the least. There was no significant difference between the occurrence of STH parasite and the vegetable types (χ2=4.200, P=0.380). For the washed, cabbage and lettuce (4%) harboured more contamination while spinach, carrot and green paper (2.6%) have the least. Similarly, there was no significant difference between the occurrence of STH parasite and the vegetable types (χ2=3.00, P=0.558). The overall prevalence of STH infections in all the vegetables were as follows: hookworms (30.3%), Ascaris lumbricoides and Strongyloides (21.2%), Taenia sp. and Trichuris trichiura (15.2%). The results of the present study provide evidence that vegetables are potential risk factor for transmission of STH infection to human in Jama’are Metropolis, Bauchi State. Therefore, it is indispensable for retailers and consumers to proper wash their vegetables before consumption as this is necessary to reduce STH contamination.